Global Change Impacts on Forest Soils: Linkage Between Soil Biota and Carbon-Nitrogen-Phosphorus Stoichiometry - Maaroufi, Nadia I.; De Long, Jonathan R. (Frontiers in Forests and Global Change, 2020)
Forest ecosystems are subjected to global change drivers worldwide, such as increasing temperature, atmospheric carbon dioxide, nutrient pollution, as well as changes in fire and precipitation regimes. These global change drivers have greatly modified the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), which has an impact on primary productivity in forest ecosystems and in turn, affect the quality and quantity of resources entering the soil food web. However, C, N, and P soil dynamics have been mostly studied without considering their coupling effects on soil organisms. This is of critical interest because changes in nutrient stoichiometry may have a strong effect on soil biota and the ecosystem functions they drive. Further, most studies have focused on global change effects on bacteria and fungi and their C:N:P stoichiometry, while neglecting other soil organisms at higher trophic levels. This has led to an incomplete understanding of how the entire soil food web drives ecosystem processes involved in organic matter turnover and nutrient cycling. Here, we review studies that investigated how global change drivers impact C:N:P stoichiometry of soil organisms at different trophic levels in forest ecosystems and identify important knowledge gaps. We propose future directions for research on global change impacts on the linkages between soil biota and C:N:P stoichiometry.